DAISY and the trouble with LONDON - Gray, Kes; Biebow, Natascha (London : Red Fox, 2022)
"Here comes trouble! Daisy is off to actual, actual London for the day! Nanny and Grampy are taking her to see the Tower of London, Buckingham Palace, Big Ben and lots more. Trouble is, all Daisy really wants to see is Cooey the pigeon"--Publisher's description
Keywords: Daisy (Fictitious character from Gray) -- Juvenile fiction; London (England) -- Juvenile fiction; Children's stories